Jetting Phenomenon in Cold Spray: A Critical Review on Finite Element Simulations - Rahmati, S.; Mostaghimi, J.; Coyle, T.; Dolatabadi, A. (Journal of thermal spray technology, 2024)
This paper offers a concise critical review of finite element studies of the jetting phenomenon in cold spray (CS). CS is a deposition technique wherein solid particles impact a substrate at high velocities, inducing severe plastic deformation and material deposition. These high-velocity particle impacts lead to the ejection of material in a jet-like shape at the periphery of the particle/substrate interface, a phenomenon known as "jetting". Jetting has been the subject of numerous studies over recent decades and remains a point of debate. Two main mechanisms, Adiabatic Shear Instability (ASI) and Hydrodynamic Pressure-Release (HPR), have been proposed to explain the jetting phenomenon. These mechanisms are mainly elucidated through finite element method (FEM) simulations, a numerical technique rooted in continuum mechanics. However, it is important to emphasize that FEM is limited by the equations established for analysis, and as such, its predictive capabilities are confined to those principles clearly defined within these equations. The choice of employed equations and approaches significantly influence the outcomes and predictions in FEM. While recognizing FEM's capabilities, this study reviews the ASI and HPR mechanisms within the context of CS. Additionally, this paper reviews FEM's algorithms and the core principles that govern FEM in calculating plastic deformation, which can lead to the formation of jetting.